A Compartmentalization & Ventilation System Retrofit Strategy for High-Rise Residential Buildings in Cold Climates. (October 2017) - Carlsson, Mathew; Touchie, Marianne; Richman, Russell
Abstract: This research proposes a rehabilitation strategy for aging high-rise residential buildings involving suite compartmentalization and a modified ventilation strategy. The impact of this retrofit strategy on energy consumption and fuel mix is investigated through computer simulation using a calibrated EnergyPlus model of a case study building. Findings show a 51% (48.5 ekWh/m 2 ) reduction in overall annual heating energy for the building, with electrical space heating energy decreasing by 20% (10.5 kWh/m 2 ), and natural gas consumption for mechanical ventilation decreasing by 87% (38.0 ekWh/m 2 ). The building's overall annual carbon footprint decreased by 29%, or approximately 20.2 tCO2 e (3.9 kgCO2 e/m 2 ).